Attitudes towards abortion in male and female adolescents with diverse sexual and pregnancy experiences: A cross-sectional study - Hendriks, Jacqueline; Fyfe, Sue; Doherty, D.A.; Jacques, Angela; Styles, I.; Hickey, M.; Skinner, S.R. (CSIRO PUBLISHING, 2020)
© 2020 CSIRO. Background: Research focused on adolescents' attitudes towards abortion is limited, and validated scales are not routinely used. A greater understanding of adolescents' attitudes towards abortion could better inform the sexuality education strategies targeted at this age group. Methods: A cross-sectional survey was completed by 1470 adolescents (437 males, 1033 females) aged 12-19 years and living in Perth, Australia. Participants were recruited from secondary schools, antenatal clinics and termination clinics to capture varying experiences of sexual activity and pregnancy. Survey items investigated abortion attitudes, sexual behaviour and pregnancy history alongside other demographic and psychosocial factors. Analyses included comparative means and adjusted linear regressions. Results: Sexually active participants (n = 554) and females reporting a previous abortion (n = 196) held more supportive attitudes towards abortion (P < 0.001 for both). Among sexually active females, more supportive attitudes were held by those reporting a previous abortion (β = 2.60, 95% confidence interval 0.93-4.27, P = 0.002), later age (≥16 years) at first vaginal intercourse (P < 0.001), use of oral contraception at last sex (P = 0.029), previous condom use (P < 0.001) and/or three or more oral sex partners in the previous 12 months (P = 0.005). For sexually active males, more supportive attitudes were reported by those whose female partners had used oral contraception at last sex (P = 0.013) or ever (P = 0.017). Multivariable analyses indicated that other correlates, including risky sexual behaviour, had minimal or no effect on attitudes. Conclusions: Adolescents' attitudes towards abortion appear to be influenced by their ability to personalise and contextualise the effect of a pregnancy. Associations between less-effective contraceptive use and reduced support for abortion may be explained by a diminished perceived risk of parenthood. Educational strategies should acknowledge and respond to differences in abortion attitudes as adolescents commence and navigate sexual relationships.